2019
DOI: 10.5194/acp-19-12051-2019
|View full text |Cite
|
Sign up to set email alerts
|

Estimating global surface ammonia concentrations inferred from satellite retrievals

Abstract: Abstract. Ammonia (NH3), as an alkaline gas in the atmosphere, can cause direct or indirect effects on the air quality, soil acidification, climate change and human health. Estimating surface NH3 concentrations is critically important for modeling the dry deposition of NH3 and for modeling the formation of ammonium nitrate, which have important impacts on the natural environment. However, sparse monitoring sites make it challenging and difficult to understand the global distribution of surface NH3 concentratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 82 publications
(123 reference statements)
2
24
0
Order By: Relevance
“…The seven subregions are the Northeast (NE), the Midwest (MD), the Northern Great Plains (NGP), the Northwest (NW), the Southern Great Plains (SGP), the Southeast (SE), and the Southwest (SW). corn and spring wheat expansion together greatly boosted the NH 3 loss proportion, which may contribute to the decreasing crop NUE in these regions (Lu et al, 2019) (Fig. 4).…”
Section: Spatiotemporal Change In the Nh 3 Emissionsmentioning
confidence: 98%
See 1 more Smart Citation
“…The seven subregions are the Northeast (NE), the Midwest (MD), the Northern Great Plains (NGP), the Northwest (NW), the Southern Great Plains (SGP), the Southeast (SE), and the Southwest (SW). corn and spring wheat expansion together greatly boosted the NH 3 loss proportion, which may contribute to the decreasing crop NUE in these regions (Lu et al, 2019) (Fig. 4).…”
Section: Spatiotemporal Change In the Nh 3 Emissionsmentioning
confidence: 98%
“…The predictable rise in food demand may lead to more N fertilizer consumption in the coming decades (Alexandratos and Bruinsma, 2012;David et al, 1997). However, 5 %-9 % of the N applied was lost to the atmosphere through ammonia (NH 3 ) volatilization (0.5-1 Tg N annually) across the US at the beginning of this century, which lowered the N use efficiency (NUE) of crops and caused numerous environmental issues (Bouwman et al, 2002;Cassman et al, 2002;Lu et al, 2019;Tilman et al, 2002). Nationwide, synthetic Nfertilizer-induced NH 3 volatilization, contributing to 15 %-30 % of annual total NH 3 emission, has been identified as the second contributor to atmospheric NH 3 only next to livestock production (Park et al, 2004;Paulot et al, 2014;Reis et al, 2009;US EPA, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the NH 3 emissions intensity for the farmland source in this region is relatively small, which leads to a higher ratio of near-source NH 3 deposition to NH 3 emissions, and a lower ratio of long-range-transported NH 3 to NH 3 emissions. This may also be one of the reasons for the relatively low atmospheric NH 3 concentration in subtropical hilly areas (Liu et al 2019). In this study, the paddy area was relatively small, which resulted in a small source strength.…”
Section: Discussionmentioning
confidence: 79%
“…This pattern of distribution of croplands or animal farms accompanying the surrounding natural ecosystems may result in a higher near-source deposition ratio of NH 3 in the subtropical hilly region than that in the plain areas. Recent observations also showed that the concentration of NH 3 in the subtropical hilly areas of China was not very high (Liu et al 2019), which indirectly indicates that there may be a high near-source deposition of NH 3 in the subtropical hilly areas, but there is no direct experimental evidence.…”
Section: Introductionmentioning
confidence: 96%
“…However, it is challenging to quantify fertilizer-induced NH3 emissions due to the paucity of information on spatially and temporally varied environmental conditions and various agricultural practices (Behera et al, 2013;Bouwman et al, 2002;Pinder et al, 2006;Sommer et al, 2004). Inverse modeling of atmospheric observations such as N deposition and satellite images has been developed as an indirect approach to estimate seasonal NH3 emission at the regional and national scale (Gilliland et al, 2006;Liu et al, 2019)). However, this "top-down" approach has difficulty in separating contribution of each individual source of NH3 emission due to the observations contain all sources of NH3 emissions.…”
mentioning
confidence: 99%